Synthesis of glucuronides in liver homogenates - Dutton, Geoffrey John (The University of Edinburgh, 1953)
From a chemical point of view, glucuronic acid may be regarded as a derivative of glucose in which the primary alcoholic group has been oxidised, producing a carboxylic acid. The chemical properties of glucuronic acid have as yet been relatively little studied, but like all substances bearing a potentially reducing aldehyde group, it will form glycosides, and these 'conjugated' compounds, without reducing properties, are known as glucuronides.

In living organisms, glucuronic acid is found almost entirely in the conjugated form, and, although very widely distributed, remarkably little is known about its physiological function. As the great importance of the compound can be inferred from such widespread occurrence we may, before considering the various theories regarding its biosynthesis, briefly indicate the natural distribution of glucuronic acid.

The work presented below was begun with the intention of studying further the nature of glucuronide synthesis in the liver, using disintegrated cell preparations (the so- called 'homogenates'); the use of such preparations is the next logical step after slice experiments, for it enables more consistent conditions to be attained, and prepares for eventual enzyme isolation.

In place of the overall results which are all that can be ascertained from experiments on whole animals, the homogenate technique offers a simple and convenient method of directly demonstrating definite reactions, such as the production of o-aminophenylglucuronide on adding o-aminophenol. Whereas with the intact animal, its perfused organ or even slices of that organ, there is no certainty that the added substance is really reaching the responsible enzymes, or in what form or concentration it might do so, in the homogenate technique a much closer control can be exercised. The problems of diffusibility of substrate and inhibitors through the cell membrane, or of unequal tissue thicknesses with their consequent metabolic differences, do not exist in homogenates, where, provided reasonably complete cell disruption has occurred, equal volumes of the tissue preparation will behave identically, being to the same degree exposed to their environment. If the homogenate be used in a sufficiently dilute form, autolysis will be checked and by the addition of various metabolites and cofactors the enzyme system of part or all of the desired reaction may be encouraged above the level of others; subsequently the studied system may be isolated from the crude homogenate and its behaviour controlled to an extent impossible by any other means.

Therefore, since liver slices had already been used by Storey to investigate the biosynthesis of glucuronides, liver homogenates were employed in the present work, which continues the study of glucuronic acid conjugation in the liver.

It was found during the course of this work that appreciable glucuronide formation could be obtained in liver homogenates, but only when a boiled liver extract was added to the medium (Dutton & Storey, 1951). The bulk of this work, then, concerns the isolation and purification of the substance responsible, and the behaviour of the enzyme system utilising it (Dutton & Storey, 1953).

After the tabulation of the various standard methods used, there follows a report of the experimental results, showing how, despite the trial of many compounds of metabolic importance, no significant synthesis was obtained unless a boiled liver extract containing the unknown factor was added. Evidence that the products of synthesis were indeed glucuronides is given, and a few observations on the homogenate enzyme are appended. Work on the nature of this synthesis with the crude factor is then described, and the dissimilarity of the system to that obtaining with sliced tissue (Storey, 1950) pointed out. Lastly, the course of isolation and purification of the factor is illustrated, with its analysis and structural investigation. In the Discussion the relationship of this work to the results of previous investigators will be dealt with, and its bearing on the wider aspects of glucuronic acid metabolism indicated.